Strengths, Opportunities and Challenges of Health Transformation Plan as a Policy of Universal Health Coverage: A Qualitative Study in Kurdistan - Ahmad Pourmoradi; Peigham Heidarpoor (Shahid Sadoughi University of Medical Sciences, 2023)
Background: In 2014, the Iranian Ministry of Health and Medical Education (MOHME) has introduced Health Transformation Plan (HTP) to guarantee the provision of high-quality healthcare services. This study aimed to determine the viewpoint of policy-makers, and health system managers affiliated to Kurdistan University of Medical Sciences about the opportunities and challenges of this plan. Methods: In this qualitative case study, a purposive sampling method was used to select study experts in the field of health system. Research data was collected through semi-structured interviews with 18 participants and two focus group discussions associated with health-care reform issues with policy-makers, and health system managers of the province. Data was analyzed using content analysis method and MAXQDA 10.0 software. Results: As a whole, study findings revealed 8 main themes and 19 sub-themes and 156 codes regarding HTP factors. Three themes were dedicated to opportunities, strengths and opportunities, with seven subthemes and four themes were dedicated to stewardship, Cultural and educational, infrastructural, staffing and service delivery challenges with twelve subthemes. Conclusion: The HTP should include effective interventions to overcome existing challenges in the provision of healthcare services through establishing new health facilities, offering recruitment and retention incentives for healthcare professionals, expanding primary health care services to urban and peri-urban as well as rural and remote areas.